2018
DOI: 10.1186/s13068-018-1292-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of untreated lignocellulosic feedstock is independent of S-lignin composition in newly classified anaerobic fungal isolate, Piromyces sp. UH3-1

Abstract: BackgroundPlant biomass is an abundant but underused feedstock for bioenergy production due to its complex and variable composition, which resists breakdown into fermentable sugars. These feedstocks, however, are routinely degraded by many uncommercialized microbes such as anaerobic gut fungi. These gut fungi express a broad range of carbohydrate active enzymes and are native to the digestive tracts of ruminants and hindgut fermenters. In this study, we examine gut fungal performance on these substrates as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
0
17
0
1
Order By: Relevance
“…Piromyces sp. UH3-1 recognizes the secretion of lignin-regulating enzymes by the fungal pathway and is capable of producing a more efficient enzyme mixture (Hooker et al 2018). Denman and coworkers have found that Orpinomyces had higher abundance with grain feed compared to fiber diets (Denman et al 2008).…”
mentioning
confidence: 99%
“…Piromyces sp. UH3-1 recognizes the secretion of lignin-regulating enzymes by the fungal pathway and is capable of producing a more efficient enzyme mixture (Hooker et al 2018). Denman and coworkers have found that Orpinomyces had higher abundance with grain feed compared to fiber diets (Denman et al 2008).…”
mentioning
confidence: 99%
“…A previous study has shown that Neocallimastix is efficient in straw silage cell wall digestion [ 40 ], and it showed high polysaccharide hydrolase and esterase activity [ 41 ]. Piromyces could regulate the secretion of lignin-regulating enzymes via the fungal pathway and is capable of producing effective enzyme complex [ 42 ]. Screening of the microbial CAZyme transcripts indicated that the anaerobic fungi Neocallimastigaceae produced the largest share of cellulase transcripts [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, lignin is predominantly made up of guaiacyl and syringyl monomers, where the former is less crosslinked than the latter and in comparison, is an easier lignin-monomer to breakdown. Syringyl-rich lignin has also been shown to negatively impact the growth of some lignindegrading fungi (Hooker et al, 2018). It might be the case that the monomeric composition of lignin plays an important role in the success of peroxidase treatment, whereby wastes with high syringyl monomeric units (e.g.…”
Section: General Discussion Of Bacterial and Enzyme Experimentsmentioning
confidence: 99%